Dispute Settlement in Maritime Law - The Effectiveness of the International Tribunal for the Law of the Sea in Resolving Maritime Disputes - Nighy,Stina (2024)
The International Tribunal for the Law of the Sea (ITLOS), established under the United Nations Convention on the Law of the Sea (UNCLOS), plays a vital role in resolving disputes about maritime law. As the world’s oceans become more important for trade, resources and environmental stability, ITLOS provides a specialized legal framework to address conflicts. This thesis examines how effective ITLOS is at enforcing its judgments and compares it to other dispute settlement mechanisms under UNCLOS. Using a legal analytical and dogmatic method, the essay explores the strengths and weaknesses of ITLOS through a comparative analysis and case study. ITLOS is effective in procedural disputes like the prompt release of vessels, where compliance rates are high. However, in politically sensitive cases, such as The Arctic Sunrise case, where state sovereignty and power dynamics play a role, compliance is lower. In contrast, cases like The Bay of Bengal Maritime Boundary Dispute show ITLOS’s ability to resolve complex disputes peacefully when the states involved operate on more equal footing. The thesis also compares ITLOS with other dispute resolution mechanisms under UNCLOS, such as arbitration and the International Court of Justice (ICJ). Arbitration is more flexible but depends on state cooperation, which can lead to mixed results, as seen in The South China Sea Arbitration. The ICJ, while influential and respected globally, lacks ITLOS’s specialization in maritime law, making ITLOS better suited for technically complex issues. The result of the investigation shows that ITLOS is an important but limited mechanism. Its effectiveness depends not just on its legal expertise but also on the willingness of states to comply with its rulings. Comparisons with other mechanisms show that each has strengths and challenges, with ITLOS’s specialization being its main advantage. However, broader issues in international law, such as power imbalances and the lack of enforcement mechanisms, continue to affect all judicial bodies, including ITLOS.
Keywords: Public International Law